Twitter in Marketing Practice of the Religious Media. An Empirical Study on Catholic Weeklies in Poland - Leonowicz-Bukała, Iwona (Religions, 2021)
This article presents the partial conclusion of the research project devoted to marketing activity of Polish Catholic opinion-forming weeklies on the social media platforms. The main aim of this article is to present the results of the study on the use of Twitter as a marketing tool by Polish nationwide Catholic opinion-forming weeklies. The basic research questions concerned the extent of utilizing the platform by the magazines’ editors to create and distribute the content of their media product, maintain and develop brand communication and self-promotion. The case studies and the content analysis of the accounts of the three magazines—Gość Niedzielny, Tygodnik Katolicki Niedziela and Przewodnik Katolicki—show that there are three different ways in how the editors of the magazines understand the role of the Twitter account of the title they represent—as an ‘active communicator’, ‘active communicator and community supporter’ or ‘community supporter’. The conclusions show that the studied media fairly efficiently use the visual and distributional potential of the platform as well as some of its features, at the same time missing the chance to build a brand-loyal community. They also limit the role of Twitter to that of a supplement for the main communication channel, which is the printed weekly and its website.